Implementasi fuzzy analytical hierarchy process pada perangkingan pencapaian belajar siswa - Widayanti, Lilis (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2025)
One of the important components in determining the right learning strategy is the assessment of student learning achievement. At SMK PGRI 3 Sidoarjo, assessments are not only carried out on academic aspects, but also pay attention to social, spiritual, skills, knowledge, and attendance aspects. However, the assessments carried out still use a system using direct weighting. The ranking system using direct weights has a weakness of subjectivity in the weights based on the assessor's intuition so that the results are less objective. Fuzzy Analytical Hierarchy Process (AHP) can increase objectivity in conducting rankings because the weights become more proportional. This study aims to implement Fuzzy AHP for assessing student learning achievement at SMK PGRI 3 Sidoarjo. This study contributes to the literature on the application of the Fuzzy AHP approach in student ranking and may serve as a foundation for the advancement of increasingly complex decision support systems in academia. The variables involved in Fuzzy AHP for student ranking are social attitude, spiritual attitude, skills, knowledge, and attendance. The final results of the study indicated that the fuzzy AHP based student ranking system produced a match of 45%, with a mismatch rate of 55% compared to the direct weighting system. This indicates that the Fuzzy AHP method is indeed different from the direct weighting system in terms of objectivity. The difference in results is due to the approach in determining the weight of different criteria.